Emerging Technologies in Computing c - Miraz, Mahdi H.; Excell, Peter; Ware, Andrew; Soomro, Safeeullah; Ali, Maaruf; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book constitutes the refereed conference proceedings of the First International Conference on Emerging Technologies in Computing, iCEtiC 2018, held in London, UK, in August 2018. The 26 revised full papers were reviewed and selected from more than 59 submissions and are organized in topical sections covering Cloud, IoT and distributed computing, software engineering, communications engineering and vehicular technology, AI, expert systems and big data analytics, Web information systems and applications, security, database system, economics and business engineering, mLearning and eLearning. .
Keywords: Computer communication systems; Special purpose computers; Computer security; Computer Communication Networks; Special Purpose and Application-Based Systems; Systems and Data Security